PERANCANGAN PROTOTYPE WEBSITE DESA NAGREG KENDAN KABUPATEN BANDUNG SEBAGAI DESA WISATA - Aura Levyka, Gabrielle; Denny Nugraha, Novian; Soedewi, Sri (eProceedings of Art & Design, 2024)
Nagreg Kendan Village, in Bandung Regency, is a pioneering tourism village thatwas formed after the expansion of Nagreg Village. Now 12 years old, the village is part of the Bandung Regency Tourism Village Program. Famous for the Kendan Kingdom Site,Nagreg Kendan Village has a variety of natural and cultural potential, easily accessible via transportation from Bandung Regency. Despite its great tourism potential, a lack of publicexposure has resulted in limited visitation to the village. Suboptimal media management is a contributing factor to the lack of public knowledge about Nagreg Kendan Village.Therefore, further research was conducted on this village to increase public knowledgeand interest in visiting this village. The research method used is a qualitative researchmethod, with 2 stages used in conducting research. The first stage is data collectionthrough observation and interviews as primary data, and conducting literature studies assecondary data. The second stage is to analyze the data. Theresults showed that furtherefforts are needed in utilizing information media to provide comprehensive informationabout the tourism and industrial potential of Nagreg Kendan Village, Bandung Regency so that more people know and are interested to visit this village. Keywords: website, information media, user interface and user experience design, tourism village.